Analysis of critical thinking skills of primary students in IPAS learning - Dian Fitriyanti; Alif Mudiono; Oktaviani Adhi Suciptaningsih (Journal of Research in Instructional, 2025)
21st century abilities are required to face the challenges, problems, living, and careers of the modern age. These abilities include critical thinking, creativity, communication, and collaboration (4C). In the context of problem-based learning in IPAS (Natural and Social Sciences) education, critical thinking is quite relevant. The goal of this study is to examine the critical thinking abilities of fifth-grade students in IPAS learning. This study applies a quantitative approach to investigate data in real world settings. The study includes 27 fifth-grade students from a public primary school in Blitar Regency, East Java. The instrument utilized is a descriptive test sheet that measures five components of critical thinking as defined by Ennis: offering simple explanations, developing basic abilities, drawing conclusions, providing additional explanations, and developing strategies and tactics. These five components are further expanded into ten indications of critical thinking ability. The analysis’s findings indicate that students’ typical critical thinking abilities are divided into three categories: medium category 10%, low category 60%, and extremely low 30%. These insights can be used to build more effective learning innovations that improve students' critical thinking skills.